MODERN TRENDS IN ASSESSING THE IMPACT OF INDUSTRIAL DEVELOPMENT ON THE ENVIRONMENT (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article explores the social psychological characteristics of marital satisfaction in pure and mixed-culture families. It examines how cultural similarities in pure culture families contribute to mutual understanding and shared expectations, while cultural differences in mixed-culture families introduce unique challenges. The article emphasizes the importance of intercultural competence, adaptability, and effective communication in achieving marital satisfaction in mixed-culture families, offering insights into how couples can navigate cultural differences to build strong, satisfying relationships